ATIONALISM AND INTERNATIONALISM WITHIN THE SYSTEM OF IVAN FRANKO’S HISTORICAL AND PHILOSOPHIC VIEWS - Holod, R. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is dedicated to the problem of Franko’s perception of the idiologems «nationalism» and «internationalism» as related historical and philosophic categories including the evolution of the view of the world and philosophic systems and beliefs of the writer. The problem of I. Franko’s attitude towards the dialectics of «national» and «international» in the cultural, political, economic and other contexts is being studied.